The next generation of Nucleus® fitting: A multiplatform approach towards universal cochlear implant management. (July 2013) - Botros, Andrew; Banna, Rami; Maruthurkkara, Saji
Abstract Objective: This article provides a detailed description and evaluation of the next Nucleus® cochlear implant fitting suite. A new fitting methodology is presented that, at its simplest level, requires a single volume adjustment, and at its advanced level, provides access to 22-channel fitting. It is implemented on multiple platforms, including a mobile platform (Remote Assistant Fitting) and an accessible PC application (Nucleus Fitting Software). Additional tools for home care and surgical care are also described. Design: Two trials were conducted, comparing the fitting methodology with the existing Custom Sound™ methodology, as fitted by the recipient and by an experienced cochlear implant audiologist. Study sample:Thirty-seven subjects participated in the trials. Results: No statistically significant differences were observed between the group mean scores, whether fitted by the recipient or by an experienced audiologist. The lower bounds of the 95% confidence intervals of the differences represented clinically insignificant differences. No statistically significant differences were found in the subjective program preferences of the subjects. Conclusions: Equivalent speech perception outcomes were demonstrated when compared to current best practice. As such, the new technology has the potential to expand the capacity of audiological care without compromising efficacy.